Optimization of taste-masking on ibuprofen microspheres with selected structure features - Wei Qin; Yuanzhi He; Zhen Guo; Liu Zhang; Li Wu; Xianzhen Yin; Shailendra Shakya; Abi Maharjan; Yan Tang; Weifeng Zhu; Jiwen Zhang (Elsevier, 2019)
The microsphere was a primary particulate system for taste-masking with unique structural features defined by production process. In this article, ibuprofen lipid microspheres of octadecanol and glycerin monostearate were prepared to mask the undesirable taste of ibuprofen via three kinds of spray congealing processes, namely, air-cooling, water-cooling and citric acid solution-cooling. The stereoscopic and internal structures of ibuprofen microspheres were quantitatively analyzed by synchrotron radiation X-ray micro-computed tomography (SR-µCT) to establish the relationship between the preparation process and microsphere architectures. It was found that the microstructure and morphology of the microspheres were significantly influenced by preparation processes as the primary factors to determine the release profiles and taste-masking effects. The sphericity of ibuprofen microspheres congealed in citric acid solution was higher than that of other two and its morphology was more regular than that being congealed in air or distilled water, and the contact angles between congealing media and melted ibuprofen in octadecanol and glycerin monostearate well demonstrated the structure differences among microspheres of three processes which controlled the release characteristics of the microspheres. The structure parameters like porosity, sphericity, and radius ratio from quantitative analysis were correlated well with drug release behaviors. The results demonstrated that the exterior morphology and internal structure of microspheres had considerable influences on the drug release behaviors as well as taste-masking effects. Keywords: Ibuprofen microsphere, Spray congealing, Internal structure, Synchrotron radiation X-ray micro-computed tomography